Bullying and self-esteem in students of the second year of secondary school from the district of Lurin - Cuya Zavaleta, Mayra Fernanda (2021)
The purpose of this study was to determine the relationship between the dimensions of bullying and self-esteem. The research design was descriptive correlational. The study populationconsisted of 139 second year secondary school students from a school in the district of Lurín. A non-probabilistic, intentional sample consisting of 98 participants was used. The instrumentsused were Bullying and School Violence test by Oñate and Piñuel, validated by Aranda in 2010 (Cronbach’s Alpha = 0.93) and Coopersmith’s Self-Esteem Inventory, validated by Mesías in2017 (Cronbach’s Alpha = 0.799), both in Peru. The results show a correlation between the global bullying index and general self-esteem with a Spearman correlation coefficient (-0.485**).It is concluded that there is a significant relationship between both variables.